Developing Home Service System; Business Process Reengineering for Motorcycle Workshop - Windarto, Yudhi; Hersant, Rebecca; Putro, Endi (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2021)
Business Organizations always strive for their self to reach business sustainability. There are various dynamic challenges in business environment that must be respond by each organization. Organizational responds for each challenge very decisive to organization’s business sustainability in the future. For now, in this Covid 19 pandemic situation each organization must creative and innovative to change and modify their business model in order to survive. Motorcycle workshop was one of the SME that affected by Covid 19 pandemic, because government policy to restriction activity of people and social distancing. Decreasing customers of motorcycle workshop and to respond the situation bring up the idea to reengineering business model. Home service system was selected as alternative solution to strive for survive in this situation, of course, by implementing a good health protocol. This system was built with a mobile application as a tool in reservation and managing customers service schedules. With this system customers do not have to come and queue at the workshop, so it will be safer in this pandemic situation. Not all services can be served with this system, only minor, moderate and routine repairs that can be served with this system. The payment transaction process is carried out on the spot according to the calculations by the system. With this new business process model, it is hoped that it will be the right solution for consumers and workshops so that they can remain productive in the midst of the Covid 19 pandemic.